Rancang Bangun Sistem Keamanan Dan Monitoring Suhu Serta Kontrol Lampu Kandang Ayam Broiler Berbasis Internet Of Things (IoT) - Egas De Jesus Martins Corbafo; Yoseph P. K. Kelen; Budiman Baso; Willy Sucipto (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2023)
In this research, a tool was designed to help chicken farmers in their daily farming activities. The common problems faced by chicken farmers are theft and the need to manually check the temperature inside the coop. Therefore, a Security and Temperature Monitoring System as well as Broiler Chicken Coop Lamp Control Based on the Internet of Things (IoT) was created using Arduino Uno as the controller for the entire system. The tools used in this system are Arduino Uno, HC-SR04 Ultrasonic sensor, Buzzer, DHT22, 16x2 LCD, ESP8266, Breadboard, Relay, and Incandescent Lamp. The method used to create this tool is the engineering design method in the automation system. The test results showed that the system was able to maintain the temperature inside the chicken coop according to the ideal conditions for Broiler chickens.